2016
DOI: 10.1063/1.4965254
|View full text |Cite
|
Sign up to set email alerts
|

Prompt gamma ray diagnostics and enhanced hadron-therapy using neutron-free nuclear reactions

Abstract: We propose a series of simulations about the potential use of Boron isotopes to trigger neutron-free (aneutronic) nuclear reactions in cancer cells through the interaction with an incoming energetic proton beam, thus resulting in the emission of characteristic prompt gamma radiation (429 keV, 718 keV and 1435 keV). Furthermore assuming that the Boron isotopes are absorbed in cancer cells, the three alpha-particles produced in each p-11 B aneutronic nuclear fusion reactions can potentially result in the enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Recently, much interest has focused on using the α particles generated by such reaction for cancer treatments in human bodies. According to Yoon et al [15] and Giuffrida et al [16], based on Monte Carlo simulations, cancer treatment using the pB reaction could produce an enhancement of the treatment biological effectiveness, if compared with standard proton therapy. Experimental campaigns conducted in-vivo on boron-treated cancer cells by Cirrone et al [17] demonstrated the potential clinical efficacy of this approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, much interest has focused on using the α particles generated by such reaction for cancer treatments in human bodies. According to Yoon et al [15] and Giuffrida et al [16], based on Monte Carlo simulations, cancer treatment using the pB reaction could produce an enhancement of the treatment biological effectiveness, if compared with standard proton therapy. Experimental campaigns conducted in-vivo on boron-treated cancer cells by Cirrone et al [17] demonstrated the potential clinical efficacy of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Petringa et al [18,19] proposed that prompt γ 's emitted in the pB reactions could be used for on-line proton beam imaging purposes during cancer treatment, also reported in Refs. [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated by MCNP6 simulations that the proton-boron fusion reaction rate at clinically relevant boron concentrations (100 ppm) is too small in order to have any measurable impact on the absorbed dose. Other groups stated as well, that the magnitude of dose increase using realistic boron concentration values remains under 10 % and the dose increase occurs mainly due to the composition and the density changes instead of alpha particle contribution [23][24][25]. The additional physical dose from BPF reaction calculated around 0,3 %.…”
Section: Boron Proton Fusion Enhanced Proton Therapy (Bpfept)mentioning
confidence: 99%
“…The highest probability for the most effective combination of BPC and proton dose occurs at a discrete proton energy level of 675 keV (5)(6)(7)(8)(9). Accessing this energy requires an initial proton deceleration to a certain position along the proton dose-depth curve (under the Bragg peak or at the end of the spread of the Bragg peak) and thus the BPC reaction can be defined with submillimeter accuracy.…”
mentioning
confidence: 99%